Antioxidant and stress-adaptive properties of putative probiotic bacteria in Pakistani fermented buffalo milk - Saleem, Gulnaz; Rao, Bisma; Khaskheli, Gul Bahar; Qu, Hengxian; Ahamed, Md Shabuddin; Qasim, Muhammad; Gu, Ruixia; Chen, Xia (Frontiers in Nutrition, 2025)
IntroductionFermented buffalo milk products from South Asia remain an underexplored source of microbial diversity with potential health-promoting benefits. This study investigates the probiotic and industrial suitability of lactic acid bacteria (LAB) and non-LAB isolates from traditional Pakistani dairy, addressing gaps in region-specific probiotic discovery.MethodsForty-seven bacterial isolates were obtained from fermented buffalo milk products (yogurt and cheese). Molecular identification (16S rRNA sequencing) classified isolates into LAB and non-LAB taxa. Probiotic potential was evaluated via in vitro assays for gastrointestinal stress tolerance (pH 2.0, 0.5% bile), antioxidant activity (DPPH scavenging), and industrial adaptability (growth at 4–45°C, 2–6% NaCl).ResultsEight strains were prioritized, including Lactobacillus plantarum Y1, L. brevis Cc3, Streptococcus thermophilus Y6/Cc1/Cm5, and non-LAB Bacillus dendritiformis Y9. L. plantarum Y1 exhibited exceptional acid resistance (>5.0 log10 CFU/mL at pH 2.0) and bile tolerance (6.5 log10 CFU/mL). L. brevis Cc3 combined high bile resilience (6.0 log10 CFU/mL) with robust antioxidant activity (52% DPPH scavenging), while S. thermophilus Y6 showed 48% antioxidant capacity. Non-LAB isolates, particularly B. dendritiformis Y9, demonstrated unexpected bile stress survival (5.4–5.5 log10 CFU/mL). All strains grew under industrial conditions (4–45°C, 2–6% NaCl), except S. thermophilus Cc1, which was heat-sensitive above 40°C.ConclusionThis study highlights South Asian buffalo milk as a reservoir of both conventional LAB and novel non-LAB strains with dual stress tolerance and antioxidant functionality. L. plantarum Y1 and L. brevis Cc3 emerge as prime candidates for developing culturally tailored functional foods to address regional nutritional challenges. The resilience of non-traditional isolates such as B. dendritiformis Y9 challenges existing probiotic taxonomical biases, suggesting broader microbial resources for gut-health innovations. These findings advocate for integrating regionally adapted probiotics into functional diets to enhance gastrointestinal health and oxidative stress mitigation in South Asian populations.